Secondary traumatisation in psychosocial emergency care personnel: a longitudinal study accompanying German trainees - Greinacher, Anja; Nikendei, Alexander; Kottke, Renate; Wiesbeck, Jürgen; Herzog, Wolfgang; Friederich, Hans-Christoph; Nikendei, Christoph (Health and social care in the community, 2020)
Psychosocial emergency care personnel form an important first responder subgroup, in which trained volunteers provide psychological first aid to accident and trauma survivors, their relatives, eye witnesses, bystanders and first responders themselves. This is the first longitudinal study to assess psychological burden due to secondary traumatisation and relevant resilience factors in psychosocial emergency care personnel. We asked 100 German psychosocial emergency care workers to assess their feeling of preparedness and resilience factors prior training. After training, when participants had worked emergency responses, we assessed secondary traumatisation. Overall, the level of secondary traumatisation was sub-clinical (M = 37.50, SD = 5.35) after training and reported resilience factor levels were high. Three regression analyses were conducted to examine the moderation effect of preparedness on specific expertise (R2 = 0.479, p < 0.001), performance competence (R2 = 0.419, p = 0.002) and inner attitude (R2 = 0.336, p = 0.002) in regard to the relationship between resilience factors and secondary traumatisation. Feeling prepared and competent for emergency responses were protective factors. Practical implications include the following: volunteers should not take part in emergency responses if they are under excessive stress; the volunteers' resilience factors should be taken into account; emergency response training should promote the feeling of preparedness in specific expertise and performance competence.
First published: 28 December 2020
Gesehen am 01.12.2021